The Effect of Product Innovation And Service Quality On Customer Loyalty. Mediation : Customer Satisfaction (Case Study On Kopi Kenangan Customers Banjarbaru) - Diany, Adista Anjar; Rarin, Faizal Maulidhany (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research investigates the influence of product innovation and service quality on customer loyalty, with customer satisfaction serving as a mediating variable. Focusing on customers of Kopi Kenangan in Banjarbaru, the study employs a quantitative approach using a survey method. A total of 162 respondents participated, and data were gathered through structured questionnaires. The analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method via SmartPLS software. The findings reveal that both product innovation and service quality significantly and positively impact customer satisfaction and customer loyalty. Furthermore, customer satisfaction significantly contributes to customer loyalty. It also partially mediates the relationship between service quality and loyalty. Although product innovation positively affects loyalty through customer satisfaction, this indirect effect is not statistically significant